Plan Individual Fitness Training Programs for Middle-Aged Men - Karimov, F. X. (European Journal of Life Safety and Stability (2660-9630), 2021)
An effective training plan is made up individually. It takes into account personal goals, age, body type, diet, class times, and other factors.